Ovarian cancer therapeutic potential of glutamine depletion based on GS expression. (2nd April 2018) - Furusawa, Akiko; Miyamoto, Morikazu; Takano, Masashi; Tsuda, Hitoshi; Song, Yong Sang; Aoki, Daisuke; Miyasaka, Naoyuki; Inazawa, Johji; Inoue, Jun
Abstract : In ovarian cancer (OVC) cells, the cell sensitivity to glutamine (Gln) depletion is inversely correlated with the glutamine synthetase (GS) expression. GS expression was downregulated in OVC cell lines and primary tumors. The pharmacological depletion of extracellular Gln led to the inhibition of cell growth in OVC cells with low expression of GS, suggesting that these findings provide novel insight into the development of an OVC therapy based on the requirement of Gln. Abstract: Amino acids (AAs) are biologically important nutrient compounds necessary for the survival of any cell. Of the 20 AAs, cancer cells depend on the uptake of several extracellular AAs for survival. However, which extracellular AA is indispensable for the survival of cancer cells and the molecular mechanism involved have not been fully defined. In this study, we found that the reduction of cell survival caused by glutamine (Gln) depletion is inversely correlated with the expression level of glutamine synthetase ( GS ) in ovarian cancer (OVC) cells. GS expression was downregulated in 45 of 316 OVC cases (14.2%). The depletion of extracellular Gln by treatment with l -asparaginase, in addition to inhibiting Gln uptake via the knockdown of a Gln transporter, led to the inhibition of cell growth in OVC cells with low expression of GS (GS low -OVC cells). Furthermore, the re-expression of GS in GS low -OVC cells induced the inhibition of tumor growth in vitro and in vivo . Thus, these findings provide novel insight into the development of an OVC therapy based on the requirement of Gln.